Pattern Analysis of Cyber Crime Incidents to Predict Occurrence and Selection of The Best Technology to Prevent IT - Sudhesh Kumar,; Prof. Dr. Minni Sinha, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Cybercrime has become a significant global threat, affecting individuals, organizations, and governments alike. This research paper focuses on the pattern analysis of cyber crime incidents and aims to develop a predictive model to forecast its occurrence while selecting the most effective technology for prevention. Through an extensive literature review, we analyze existing research on cybercrime patterns, predictive modeling, and technologies for prevention. The study identifies the gaps in the current literature, emphasizing the need for a comprehensive approach that combines data-driven analysis with advanced cybersecurity technologies. The research methodology encompasses data collection from diverse sources, followed by rigorous data preprocessing and cleaning to ensure data quality. Machine learning algorithms and statistical methods are utilized for developing the predictive model. Evaluation metrics are employed to measure the model's performance and its ability to predict cybercrime incidents accurately. The pattern analysis of cybercrime incidents reveals various attack vectors, target sectors, and geographical distributions, providing crucial insights into the modus operandi of cybercriminals. This analysis forms the basis for building the predictive model, which can assist law enforcement agencies and cybersecurity professionals in anticipating and preventing cybercrime effectively. The findings of this research contribute significantly to the field of cybercrime prevention. The developed predictive model enhances early warning capabilities, enabling proactive measures against cyber threats. Additionally, the technology selection framework assists organizations in making informed decisions regarding cybersecurity investments.
Keywords: Cyber Crime; Pattern Analysis; Predictive Modeling; Technology Selection; Incident Prediction; Cyber Security; Machine Learning; Data Analysis; Intrusion Detection; Prevention Strategies